Biocomposite of Cellulose Nanocrystals from Nypah fruticans Wurmb with Green Synthesis Silver Nanoparticles : In situ Preparation and Antimicrobial Activity - Mailani Putri; Syukri Arief; Syukri; Gusliani Eka Putri (The Journal of Pure and Applied Chemistry Research, 2025)
Biocomposite of Cellulose Nanocrystals-Silver Nanoparticles (CNCs-AgNPs) was synthesized by in situ method using cellulose isolated from Nypa fruticans Wurmb and produced into nanomaterial scale with acid hydrolysis and silver nanoparticles (AgNPs) produced by green synthesis using Uncaria gambir Roxb leaf extract. Analysis of structure and morphology of CNCs-AgNPs biocomposite was carried out and its potential as an antimicrobial agent against Gram+ and Gram- bacteria. Characterization was carried out using UV-Vis spectrophotometer, FTIR, XRD, and TEM. The UV-Vis spectrum showed a typical Surface Plasmon Resonance (SPR) absorption peak around 420 nm which indicated the formation of AgNPs. The formed silver nanoparticles showed a Face Centered Cubic (FCC) crystal structure and were adsorbed on functional groups found on the nanocellulose surface based on XRD and FTIR analysis. The analysis results were reinforced by TEM analysis which showed that silver nanoparticles were evenly distributed on the surface of CNCs in the form of short rods with AgNPs diameters ranging from 8-10 nm and CNCs around 14 nm. Antibacterial activity showed that the CNCs-AgNPs biocomposite had the highest effectiveness against Gram+ bacteria. These results indicate the potential application of CNCs-AgNPs biocomposite as an environmentally friendly natural-based antimicrobial agent.